Henri Matisse - Welton, Jude. (New York : F. Watts, 2002)
Presents the life and works of French painter Henri Matisse in their time and place, discussing the factors that influenced his creativity and affected his career.
Includes index.
Wilson's Junior High School, November 2005
School Library Journal, January 2003
7.2
5-8
Keywords: Matisse, Henri, -- 1869-1954.; Artists -- Biography; French painting; Modern painting; Art appreciation